Development of polysulfone (PSF)-carbon molecular sieve (CMS) mixed matrix membrane (MMM) for O(2)/N(2) gas separation - Ismail, Ahmad Fauzi (Amer Inst Physics, 2009)
Mixed matrix membranes (MMMs) comprising polysulfone (PSF) Udel (R) P-1700 and synthesized carbon molecular sieve (CMS) particles (<25 mu m) have been fabricated and characterized. CMS were synthesized by using polyacrylonitrile (PAN) as polymer precursor. The casting process was performed at the processing temperature close to TB of PSF in order to maintain the flexibility of polymer during film formation. This study investigated the effects of CMS loadings (10, 20, 30 and 35wt %) on the morphology and the gas separation performance of PSF-CMS MMMs. The fabricated MMMs were characterized using TGA, DSC, FESEM and single gas permeation test using high purity O(2) and N(2). Based on FESEM micrograph, a good polymer-sieve adhesion was achieved in MMMs using the combination of PSF-CMS even at high sieve loading (up to 35 wt %). The formation of 'sieve-in-the-cage' morphology in PSF-CMS MMMs has been minimized to a great extend by implementing casting procedure at the operating temperature close to the T(g) of polymer matrix. The O(2) and N(2) permeability for MMMs were increased with increasing CMS loading; while at 20wt% CMS loading the O(2)/N(2) selectivity attain the highest value which is 5.97 with the O(2) permeability of 7.9617 barrers.